Burn Deaths: A Study on Female Victims in Manipur - Meera, Th; Nandeibam, Pabitramala; Slong, Daunipaia; Nabachandra , H (Journal of Indian Academy of Forensic Medicine, 2016)
This retrospective study was carried out in a tertiary care hospital during 2004 to 2013 to assess  the pattern of burn deaths amongst females in the State of Manipur. Out of the total 38 burn cases  brought for autopsy, 26 were female burn cases. The highest number of victims was in the age group of  21 to 30 years (53.85%). Majority of the cases were non-Manipuris (57.69%) and 84.62% of the victims  were married. The body surface area involvement of >80% was observed in 61.54%, and 57.69% of the  cases died within 24 hours. The cause of death was due to burn shock in 65.38%, and the nature of  death was accidental in 50% of the cases. History of domestic violence was present in 40% of the suicidal  deaths and in all the three cases of homicidal deaths. High mortality in young married women from burns  is attributed to dowry in rural India. Dowry system is almost non-existent in the State of Manipur, and it is  reflected in the present study where majority of the female victims of burns were non-Manipuris residing in  this State.
Keywords: Female; Burn; Nature of Death; Dowry; Non-Manipuri